Feasibility of Intensive Multimodal Therapy in Infants Affected by Rhabdoid Tumors – Experience of the EU-RHAB registry - Seeringer, A.; Bartelheim, K.; Kerl, K.; Hasselblatt, M.; Leuschner, I.; Rutkowski, S.; Timmermann, B.; Kortmann, R.-D.; Koscielniak, E.; Schneppenheim, R.; Warmuth-Metz, M.; Gerß, J.; Siebert, R.; Graf, N.; Boos, J.; Frühwald, M. C (Klinische Pädiatrie, 2014)
Rhabdoid tumors mainly affect infants and other very young children with a marked vulnerability towards intensive therapy such as invasive surgery, high dose chemotherapy (HDCT) and dose intense radiotherapy. Radiotherapy (RT) is a promising option in rhabdoid tumors but its application in infants remains controversial. Neurocognitive and vascular side effects occur even long after completion of therapy. Therapeutic recommendations suggested by the European Rhabdoid Registry including RT, high dose chemotherapy (HDCT) and methotrexate (MTX) were developed by a consensus committee. Unique to our EU-RHAB database is the ability to analyze data of 64 of 81 registered infants (under one year of age) separate from older children. 20 (age at diagnoses 2–12 months) of these had received radiotherapy. To our knowledge, this is the first report specifically analyzing treatment data of infants suffering from malignant rhabdoid tumors. Our results suggest that radiotherapy significantly increases the mean survival time as well as the 3 year overall survival in infants. We detected a doubling of survival times in infants who received RT. Overall, our results suggest that infants benefit from RT with tolerable acute side effects. Severe long term sequelae likely due to intraventricular MTX and/or RT were reported in 4 patients (leukoencephalopathy). No differences in chemotherapy-related toxicity were observed between infants and children. We suggest that a nihilistic therapeutic approach towards young infants is not warranted and that RT may not be a priori rejected as a therapeutic option in infants.
Keywords: rhabdoid tumors; AT/RT; infants; radiotherapy